Gut Microbiota Dynamics, Growth Performance, and Gut Morphology in Broiler Chickens Fed Diets Varying in Energy Density with or without Bacitracin Methylene Disalicylate (BMD) - Deborah Adewole; Fisayo Akinyemi (Microorganisms, 2021)
High-energy-density diet could increase body weight at the expense of the intestinal health of the animals. In order to optimize production without negatively influencing the gut health of chickens, dietary supplementation with bacitracin methylene disalicylate (BMD) is a common feeding strategy adopted to enhance production performance and intestinal health. Studies have suggested that BMD could improve chicken growth performance and gut health through modulation of the gut microbiota. The current study investigated the effect of BMD supplementation in a normal-energy (NE) or high-energy (HE) diet on growth performance, organ weights, jejunal morphology, and gut microbiota of broiler chickens at different growth stages. Birds were allocated to four treatments: normal-energy basal diet (NE-BAS), normal-energy BMD diet (NE-BMD), high-energy basal diet (HE-BAS), and high-energy BMD diet (HE-BMD). In the starter phase, body weight and body weight gain were reduced significantly (p < 0.05) in chickens fed HE diets compared to those fed NE diets. The FCR was significantly higher (p < 0.05) in birds fed HE-BMD diets in the starter phase but lower (p < 0.05) during the grower phase when compared to other treatments. Moreover, the relative bursa weight increased significantly (p = 0.0220) among birds that received HE diets. Birds fed HE-BMD had greater villus height (p = 0.054) than NE-BMD group. Among the chickens fed the HE diets, those that received BMD treatment had a significantly increased (p = 0.003) villus width (13.3% increase) compared to those that received the basal diet. Improved population of Firmicutes was observed in chickens fed HE-BMD diet when compared to HE-BAS. Our results imply that BMD may be more effective in improving intestinal health when supplemented in a high-energy diet for broiler chickens.